PERAN PESANTREN DALAM MEMBENTUK SANTRI YANG BERKARAKTER PLURALIS - Saifullah Saifullah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2024)
Pesantren as a traditional Islamic institution for studying, understanding, embodying, and practicing Islamic teachings, with an emphasis on the importance of character and morals as daily guidelines. One of the characteristics emphasized at Pondok Pesantren Tebuireng is a pluralist character, which according to Nurcholis Majid, pluralism is tolerance. The objectives of this research are to determine the characteristics of students at Pesantren Tebuireng Jombang; to understand the role of Pesantren Tebuireng Jombang in shaping students with pluralist characters; and to identify the supporting and inhibiting factors in the role of Pesantren Tebuireng Jombang in shaping students with pluralist characters. This research is a qualitative case study. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve Data Reduction, Data Display, and Verification. Data validity is checked through extension of observation, increased diligence, triangulation, and peer discussion. The results of the study show that the characteristics of students at Pesantren Tebuireng are sincerity, honesty, hard work, responsibility, tolerance, high solidarity, and humility; the role of Pesantren Tebuireng in shaping students with pluralist characters includes providing education to all students and offering habituation activities that support pluralist characters, in addition to the caregivers and scholars providing examples as role models for the students; supporting factors include Pesantren Tebuireng Jombang being a nationally recognized pesantren, allowing non-Muslim religions to study at Pesantren Tebuireng, having regional organizations, embodying fundamental values that shape students with pluralist characters, and prioritizing social society in general. The inhibiting factors include the pesantren being unstructured in providing education about the importance of having a pluralist character and a lack of socialization of the pesantren's vision and mission to all its elements.